The importance of emotional stability in secondary school teachers' language teaching to fulfill the needs of the national education philosophy - Saidy, Endang Pertiwi; Hassan, Aminuddin; Abd. Rahman, Fadzilah; Ab. Jalil, Habibah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Teachers hold high responsibilities where their job scopes require high sense of trustworthiness and sincerity. As a role model, teachers should show a good example to students in order to produce balanced human capital as has been objectified by the National Education Philosophy. In order to achieve this objective, teachers need to have high emotional stability. This paper will discuss the importance of teachers' emotional stability in influencing language teaching in secondary schools. This is because teachers' emotional stability is very important as it will influence students' level of achievement in language learning. Those aspects will be examined deeply through the discussion of this study by referring to the adaptation of Goleman's (1998) quetionnaires that were based. On various dimensions such as self awarenss, self control, motivation, emphathy, and social skills. The awareness of this importance will ensure teachers' emotional stability is given serious emphasis as teachers function as individuals who contribute towards the success and excellence of students.